A measurement of Hubble's Constant using Fast Radio Bursts. Issue 4 (8th September 2022) - James, C W; Ghosh, E M; Prochaska, J X; Bannister, K W; Bhandari, S; Day, C K; Deller, A T; Glowacki, M; Gordon, A C; Heintz, K E; Marnoch, L; Ryder, S D; et al.
ABSTRACT: We constrain the Hubble constant H 0 using Fast Radio Burst (FRB) observations from the Australian Square Kilometre Array Pathfinder (ASKAP) and Murriyang (Parkes) radio telescopes. We use the redshift-dispersion measure ('Macquart') relationship, accounting for the intrinsic luminosity function, cosmological gas distribution, population evolution, host galaxy contributions to the dispersion measure (DMhost ), and observational biases due to burst duration and telescope beamshape. Using an updated sample of 16 ASKAP FRBs detected by the Commensal Real-time ASKAP Fast Transients (CRAFT) Survey and localized to their host galaxies, and 60 unlocalized FRBs from Parkes and ASKAP, our best-fitting value of H 0 is calculated to be $73_{-8}^{+12}$ km s −1 Mpc −1 . Uncertainties in FRB energetics and DMhost produce larger uncertainties in the inferred value of H 0 compared to previous FRB-based estimates. Using a prior on H 0 covering the 67–74 km s −1 Mpc −1 range, we estimate a median ${\rm DM}_{\rm host}= 186_{-48}^{+59}\, {\rm pc \, cm^{-3}}$, exceeding previous estimates. We confirm that the FRB population evolves with redshift similarly to the star-formation rate. We use a Schechter luminosity function to constrain the maximum FRB energy to be log10 E max $=41.26_{-0.22}^{+0.27}$ erg assuming a characteristic FRB emission bandwidth of 1 GHz at 1.3 GHz, and the cumulative luminosity index to be $γ =-0.95_{-0.15}^{+0.18}$ . We demonstrate with a sample of 100 mock FRBs that H 0 can be measured with an uncertainty of ±2.5 km s −1 Mpc −1, demonstrating the potential for clarifying the Hubble tension with an upgraded ASKAP FRB search system. Last, we explore a range of sample and selection biases that affect FRB analyses.